(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
This article scientifically describes the external and internal morphological structure of the saxaul tree belonging to the genus Haloxylon, as well as its ecological adaptation mechanisms, distribution range, and economic importance. The study analyzes the physiological characteristics of saxaul that enable it to thrive in desert conditions, on saline and water-scarce soils. The article provides updated information based on recent scientific research about the saxaul’s ability to capture dust, sequester carbon, and function as a natural biofilter. The paper highlights the strategic ecological role of saxaul species in combating erosion and climate change in arid regions.